Altered microRNA expression in patients with sarcoidosis - Morar, Rajen; Dickens, Caroline; Dix-Peek, Therese; Duarte, Raquel; Feldman, Charles (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
BackgroundSarcoidosis is a granulomatous multisystem disease of uncertain aetiology. The disease has major inflammatory and immune components; however, the immunopathogenesis is not well understood. Micro ribonucleic acids (microRNAs) are classes of miniature, single-stranded, non-coding RNAs. Their key recognised role includes mediating the silencing of target genes post-transcriptionally. Recently, the role of miRNAs has gained interest in numerous disorders, suggested as being involved in pathogenesis of those diseases and acting as disease markers. Very little is known about the role of miRNAs in sarcoidosis, with nothing known regarding miRNAs in South African patients. The main objective, therefore, was to investigate the serum expression of approximately 800 miRNAs in patients with sarcoidosis compared with race-, age- and gender-matched healthy controls.MethodsA total of six patients and six matched controls participated in this study. Whole blood samples were collected in EDTA tubes, processed and the plasma retained. RNA was extracted from the stored plasma samples using the QIAGEN miRNeasy Mini Kit® and concentrated using a salt-ethanol precipitation. The extracted miRNA was profiled using an nCounter® miRNA human v3 expression assay and data analysed using the nSolver™ Analysis Software.ResultsAfter excluding one sample/control pair because of cellular RNA contamination, the remaining five patient and five matched control samples were analysed, and 145 miRNAs were found to be potentially differentially expressed. On applying a Bonferroni correction, the only miRNA that was significantly different was miRNA let-7a-5p, which was significantly overexpressed (141-fold change; p